(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Peatland degradation in South Kalimantan due to peatland is often considered as useless land and wasted land that can be drained and converted. This assumption is one of the main causes of peatland degradation and damage, especially in changing land use for agriculture and plantations. Government Regulation Number 71 of 2014 as amended by Government Regulation Number 57 of 2016 concerning the Protection and Management of Peat Ecosystems mandates the need to prepare a Peat Ecosystem Protection and Management Plan. This research focuses on achieving focus 1. The research method used is environmental law research that is supported by ecological and planalogical data called by Terry Hutchinson Reform-Oriented Research, namely doctrinal legal research that contains a growing taxonomy for incorporating insights from other disciplines. The findings of this study are most of the peat land in South Kalimantan is damaged due to the conversion of the area and fires. Peatland protection must be linked and harmonized with spatial planning. However, spatial planning in South Kalimantan has not been integrated with the protection of peat protected areas. Therefore, it is necessary to make a Peatland Ecosystem Protection and Management Plan as ordered by the Legislation.